ANALISIS DAMPAK DITERAPKANNYA KEBIJAKAN WORKING FROM HOME SAAT PANDEMI COVID-19 TERHADAP KONDISI KUALITAS UDARA DI JAKARTA - Umara Firman Rizi D; Suradi; Sunaryo; Andriyani Agus; Mizani Ahmad; Sheila Dewi Ayu Kusumaningtyas; Hanifah Nurhayati; Aulia Nisa’ul Khoir; Cici Sucianingsih; Nur Faris Prih W (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2019)
The purpose of this study is to examine the effect of the implementation of policies on reducing human activity regarding the covid-19 outbreak to the concentration of air pollution in March 2020 in the Jakarta area using a comparison of the time series of PM10 and PM2.5 hourly calculations calculated to be the daily average in March by applying the Pearson correlation equation and scatter diagram to obtain a pattern of relationships in the form of positive, negative or non-linear and the degree of weak, strong or perfect relationship between variables. The main contributions of this research are as follows: Evaluation of the significance of the decrease in the concentration value of the average PM10 and PM2.5 in March 2020 with a correlation to March variables in the previous year based on the acquisition of qualitative results in the form of a graph of the trend of decreasing PM10 and PM2.5 in March 2020 compared to March of the previous year and quantitative in the form of a negative correlation with the Pearson moment and scatter diagram showing a decrease in March 2020 compared to March of the previous year so that the policy of reducing human activity in a response to the Covid-19 pandemic has an impact on a better air quality condition in Jakarta.